Efektivitas Pembelajaran Daring Menggunakan E-Learning Madrasah Di Masa Pandemi Covid-19 - Ririn Eva Hidayati (Inovasi-Jurnal Diklat Keagamaan, 2021)
This research was conducted to see the effectiveness of the implementation of online learning using e-learning madrasah and to find out the inhibiting and supporting factors of using e-learning applications as a learning medium. This research is a quantitative descriptive. The data were obtained by distributing questionnaires in google form which contained closed, semi-closed, and open questions, then the data were analyzed descriptively. Respondents of this research are students and teachers of MAN 1 Kota Malang who carries out learning using e-learning applications. The results of the observation informed that 80% of respondents claimed to be able to access and use e-learning madrasah. Online learning innovations using e-learning madrasah help students undergo learning during the pandemic. The implementation of online learning using e-learning madrasah is quite effective even there is ineffectiveness in the evaluation process. Teacher professionalism is needed in online learning using e-learning madrasah in order to create fun and meaningful learning. Improving the application is also still needed to make e-learning madrasah easier to use (user-friendly). The obstacles in online learning can be overcome by the collaboration between madrasah, parents, teachers, and students.